Three versions of an inequality - Krassimir Atanassov (Notes on Number Theory and Discrete Mathematics, 2025)
Three versions of the inequality Σⁿ⁻¹ᵢ₌₁ 1/aᵢ(aᵢ₊₁+1) ≥ (n/(1+Πⁿᵢ₌₁aᵢ)) - (1/(aₙ(a₁+1))) are formulated and proved, where a₁,...,aₙ>0 are real numbers. An open problem is formulated.